Strengthening Social Capital in Indonesia: Options for the Quality Democracy & Steps to Mitigate the Latent Problem of Horizontal Conflict - Wandi Abbas; Nurhamzah Nurhamzah; Rahmisyari Rahmisyari; Khusnul Khotimah; Usmaedi Usmaedi (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
Social capital is a set of values or norms embodied in behavior that encourages the ability and capability to work together and coordinate for a significant contribution to sustainable productivity. There are three elements of social capital parameters: trust, norms and networks. Democracy has social capital in the form of freedom, equality and justice. Therefore, working democracy through social capital needs to go hand in hand. In addition, through strong social capital, conflicts between communities can be mitigated through the local wisdom of the region. This research then looks at how strengthening social capital in Indonesia can improve the quality of democracy and reduce the potential dangers of horizontal conflict in society. This research will be carried out using descriptive qualitative methods. The data used in this research comes from a literature study of research results and previous studies that are still relevant to this research. This study then found that a trust is a form of social capital that can improve the quality of democracy in Indonesia. Through a government that can be trusted, people can feel justice in a democracy. In addition, social capital through local wisdom can reduce the occurrence of social conflicts that occur in a society